Skyship Academy : crimson rising - James, Nick, 1983- (Skyship Academy ;, 2012)
When fifteen-year-old Jesse manages to smuggle onboard the Academy a mysterious red Pearl, a fragment of space debris that is a dying Earth's most important energy source, he sets forth a destructive chain of events.